ETNOCSIENCE DAKWAH ORANG BASUDARA DI MALUKU - Syarifuddin Syarifuddin (Pascasarjana IAIN Ambon, 2020)
This research deals with the study and ectnoteknology etnoscience preaching on indigenous peoples in the State Tulehu Central moluccas Province. The research problem is 1. how etnoscience collision and preaching etnoteknology with the construction of modern technology in the Moluccas; 2.how impact of modern technology on etnoscience and ectnoteknology preaching. This study uses a qualitative method. The collection technique using Focus Group dicussion and in-depth interviews on traditional leaders, and community. This study found that etnoscience and etnoteknology indigenous preaching in Tulehu very important role to provide imagery of religious social resilience to offset garbage information produced by the mass media. Etnoscience and etnoteknology preaching can prevent waste circulation of negative information that could potentially disturb the minds of people in religious teaching, understanding, and faith. Etnoscience traditions and communities in the State etnotechnology Tulehu Patawala Maluku Province (Calling People Family); system deployment or social construction at the family level by using language etno- communication. Pasaware (customary homage) is usually done in the mosque for holy days of Islam. Tabaos The statutes; Tabaos commandment serves as a medium for the publication of the social construction of the messages king was resolved in Baileo (traditional house). Through etnoscience and etnoteknology tradition to maintain, nurture, culture etno-communication as social the power tradition in Maluku. The higher the communication process etnoscience and etnoteknologi preaching in a society increasingly lower production of waste and garbage industry thinking.